2017 Charles F. Prentice Award Lecture: Peripheral Prisms for Visual Field Expansion. Issue 10 (October 2020) - Peli, Eli
Abstract : ABSTRACT: On the occasion of being awarded the Prentice Medal, I was asked to summarize my translational journey. Here I describe the process of becoming a low-vision rehabilitation clinician and researcher, frustrated by the unavailability of effective treatments for some conditions. This led to decades of working to understand patients' needs and the complexities and subtleties of their visual systems and conditions. It was followed by many iterations of developing vision aids and the techniques needed to objectively evaluate their benefit. I specifically address one path: the invention and development of peripheral prisms to expand the visual fields of patients with homonymous hemianopia, leading to our latest multiperiscopic prism (mirror-based design) with its clear 45° field-of-view image shift.